2019
DOI: 10.1111/1759-7714.13253
|View full text |Cite
|
Sign up to set email alerts
|

EGFR exon 19‐deletion aberrantly regulate ERCC1 expression that may partly impaired DNA damage repair ability in non‐small cell lung cancer

Abstract: Background: Epidermal growth factor receptor (EGFR) activating mutations are usually associated with DNA damage repair (DDR) deficiency. However, the precise mechanism has remained elusive. In this study, we aimed to investigate whether EGFR exon 19 deletion mutation downstream signals contributed to DDR deficiency by downregulation of excision repair cross-complementation group-1 (ERCC1), a key factor in DDR, expression and function. Methods: We first measured cell survival, DNA damage (γ-H2AX foci formation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Our previous report indicated that the association between the increase in 8‐OH‐dG levels due to human papillomavirus (HPV) 16/18 infection and the occurrence of EGFR mutations in patients with NSCLC might be due to a reduction in DNA repair capabilities 19 . Other groups have reported an association between lower ERCC1 expression, the SNP rs744154c in ERCC4 , and EGFR exon 19 deletion mutations, thereby revealing the possibility that EGFR exon 19 deletion mutations could be associated with decreasing DNA repair capabilities 20,21 . In the present study, we observed that EGFR deletion mutations in exon 19 were more common in patients with hOGG1 ‐Cys variants with less ability to remove 8‐OH‐dG than with hOGG1 Ser/Ser genotype.…”
Section: Discussionsupporting
confidence: 58%
“…Our previous report indicated that the association between the increase in 8‐OH‐dG levels due to human papillomavirus (HPV) 16/18 infection and the occurrence of EGFR mutations in patients with NSCLC might be due to a reduction in DNA repair capabilities 19 . Other groups have reported an association between lower ERCC1 expression, the SNP rs744154c in ERCC4 , and EGFR exon 19 deletion mutations, thereby revealing the possibility that EGFR exon 19 deletion mutations could be associated with decreasing DNA repair capabilities 20,21 . In the present study, we observed that EGFR deletion mutations in exon 19 were more common in patients with hOGG1 ‐Cys variants with less ability to remove 8‐OH‐dG than with hOGG1 Ser/Ser genotype.…”
Section: Discussionsupporting
confidence: 58%
“…This can be explained by different effects of EGFR and KRAS driver mutations on DNA repair. Driver www.nature.com/scientificreports/ mutations in EGFR are associated with decreased DNA repair capacity in non-small cell lung cancer 72 . KRAS driver mutations, on the other hand, are associated with more efficient DNA repair in lung tumors 73 which may contribute to poor response of KRAS driver mutation-positive tumors to radiotherapy 74 .…”
Section: Discussionmentioning
confidence: 99%
“…When DNA damage fails to be repaired or excised, the mutations will eventually trigger carcinogenesis. For instance, epidermal growth factor receptor (EGFR) exon 19 deletion corrected with decreased expression of ERCC1 impacts ERCC1 foci formation in response to DNA cross-link damage, contributing to DNA damage repair (DDR) deficiency ( 14 ). Germline variants of ataxia-telangiectasia mutated (ATM), tumor suppressor 53 protein (TP53), breast cancer 2 (BRCA2), EGFR, and Parkinson’s Disease-Associated protein 2 (PARK2) had been linked to cancer risk in Mendelian disorders ( 15 ).…”
Section: Introductionmentioning
confidence: 99%